Engineered procyanidin-Fe nanoparticle alleviates intestinal inflammation through scavenging ROS and altering gut microbiome in colitis mice - Chang, Yongliang; Wu, Xiawei; Lu, Shengwei; Du, Jiahao; Long, Yixiu; Zhu, Yefei; Qin, Huanlong (Frontiers in Chemistry, 2023)
Inflammatory bowel disease (IBD) is an idiopathic chronic inflammatory bowel disease characterized by inflammation, intestinal barrier injury, and imbalance of gut microbiota. Excess accumulation of reactive oxygen species (ROS) is closely correlated with the development and reoccurrence of IBD. Previous researches demonstrate that procyanidin, as a natural antioxidant, exhibits strong ability of eliminating ROS, thus showing good therapeutic effects in the inflammation-related diseases. Non-etheless, its poor stability and solubility always limits the therapeutic outcomes. Here, we typically designed an antioxidant coordination polymer nanoparticle using the engineering of procyanidin (Pc) and free iron (Fe), named Pc-Fe nanozyme, for effectively scavenging ROS and further inhibiting inflammation while altering the gut microbiome for the treatment of colitis. Furthermore, in vitro experiments uncover that Pc-Fe nanoparticles exert strong multi biomimic activities, including peroxidase, and glutathione peroxidase, for the scavenging of ROS and protecting cells from oxidative injury. In addition, the colon accumulation of Pc-Fe nanozyme effectively protects the intestinal mucosa from oxidative damage while significantly downregulates pro-inflammatory factors, repairs the intestinal barriers and alternates gut microbiome after orally administrated in sodium dextran sulfate (DSS) induced colitis mice. The results collectively illustrate that the multienzyme mimicking Pc-Fe nanozyme owns high potential for treating IBD through scavenging ROS, inhibiting inflammation, repairing gut barriers and alternating gut microbiome, which further promising its clinical translation on IBD treatment and other ROS induced intestinal diseases.